Mahuang Xixin Fuzi decoction protects the BALB/c-nude mice infected with influenza A virus by reducing inflammatory cytokines storm and weakly regulating SIgA immune response. (25th March 2023) - Liu, Meiyi; Yang, Jia; Qian, Shensi; Sun, Zhuyun; Jin, Yifan; Liu, Xiaoyun; Ye, Dongxue; Rong, Rong; Yang, Yong
Abstract : Ethnopharmacological relevance: Mahuang Xixin Fuzi Decoction (MXF), as a classical prescription of traditional Chinese medicine (TCM), has been used to treat the immunocompromised individuals infected with influenza A virus (IAV). Aim of the study: The study aims to explore the regulatory of MXF on inflammation and secretory immunoglobulin A (SIgA) antibodies immune response in BALB/c-nude mice infected with IAV. Materials and methods: The BALB/c-nude mice were infected with IAV, then different dosages of MXF were orally administrated to the mice. The weight, rectal temperature, spontaneous activity, spleen index, lung index, pathological changes of lung tissues, and the relative mRNA expression level of H1N1 M gene were measured for the purpose of valuing the antiviral effect of MXF. The expression levels of cytokines in lungs and immunoglobulin A (IgA) in serum of BALB/c-nude mice were determined with Cytometric Bead Array System (CBA). SIgA in bronchoalveolar lavage fluids (BALF) was detected with Enzyme-linked Immunosorbent Assay (ELISA). The mRNA and protein expression levels of B cell activating factor (BAFF), chemokine receptors 10 (CCR10), and polymeric immunoglobulin receptor (pIgR) in the lung tissues, which are related to the secretion of SIgA, were determined by using RT-PCR and Western blot. Results: MXF could alleviate the clinical features and reduce the severity of viral lung lesions, including improving the body weight, rectal temperature and spontaneous activity of nude mice infected with IAV, increasing spleen index, decreasing lung index, alleviating pathological damage, and decreasing the relative expression level of H1N1 M gene. Levels of pro-inflammatory cytokines, including interleukin-6 (IL-6), tumor necrosis factor-α (TNF-α), interleukin-2 (IL-2), interleukin-12p70 (IL-12p70), and interleukin-17A (IL-17A) were also significantly decreased after treatment with MXF. Interferon-γ (IFN-γ), an antiviral cytokine, was significantly up-regulated in high dose MXF (3.12 g/kg) group. Moreover, after MXF treatment, the expressions of SIgA in BALF and IgA in serum were both at relatively low levels. And the mRNA and protein expressions of BAFF, CCR10, and pIgR were significantly decreased after treatment with MXF. Conclusions: MXF has obviously protective effects on BALB/c-nude mice infected with IAV by inhibiting virus replication, calming inflammatory cytokine storm, and regulating SIgA immune response weakly. Graphical abstract: Image 1 Highlights: It was first confirmed that MXF could protect BALB/c-nude mice infected with IAV by inhibiting inflammatory cytokines. It was first discovered that MXF has weak regulation effect on SIgA immune response. This study identifies a potential therapeutic strategy for immunocompromised individuals associated with IAV.